BORING SPONGES (ICHNOGENUS ENTOBIA) IN MESOZOIC LITHOCODIUM CALCIMICROBIAL CRUSTS (Rivista italiana di Paleontologia e Stratigrafia, 2010)
Globular cavities in calcimicrobial Lithocodium crusts are interpreted as trace fossils of boring sponges belonging to the ichnogenus Entobia. Two informal groups can be differentiated: a Norian-Rhaetian group from Tabas area(NE Iran) and Adnet (near Salzburg, Austria), characterized by large chambers and broad bifurcating apertural canals, and a second group from the Aptian of central Italy presenting smaller chambers and canals. The distal ends of these canals are closed by alveolar structures, preventing water circulation and leading to the death of the sponge.